2018
DOI: 10.1186/s12894-018-0367-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use of contrast enhanced ultrasound in guiding microdissection testicular sperm extraction in nonobstructive azoospermia

Abstract: BackgroundThe aim of this study is to assess the value of contrast-enhanced ultrasound (CEUS) as a new non-invasive approach to locate the testicular area in which spermatogenesis is most likely to be found in non-obstructive azoospermic testes and to evaluate the accuracy of CEUS as a predictor of successful sperm retrieval.MethodsCEUS was performed in 120 nonobstructive azoospermia (NOA) patients. Microdissection testicular sperm extraction (M-TESE) was performed on the best and poorest perfusion areas selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Conversely, a 2018 study that utilised CEUS in 120 men with NOA and subsequent micro-TESE, demonstrated improved success rates for micro-TESE potentially due to CEUS’s ability to locate the best perfusion areas. This work suggests that CEUS can highlight microvascular distribution in testicles, aid in locating areas of best perfusion over the maximal longitudinal section, and improve success rates [ 36 ]. Lastly, work by Herwig et al [ 37 ] with patients with azoospermia undergoing TESE biopsy for retrieval of sperm showed high sperm quality in areas of high tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, a 2018 study that utilised CEUS in 120 men with NOA and subsequent micro-TESE, demonstrated improved success rates for micro-TESE potentially due to CEUS’s ability to locate the best perfusion areas. This work suggests that CEUS can highlight microvascular distribution in testicles, aid in locating areas of best perfusion over the maximal longitudinal section, and improve success rates [ 36 ]. Lastly, work by Herwig et al [ 37 ] with patients with azoospermia undergoing TESE biopsy for retrieval of sperm showed high sperm quality in areas of high tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the images that are available in real time are taken using a low-magnification microscope and the details of these images are not clear, the pictures are very ‘noisy’ [ 39 ]. Overall, while some barriers exist to the use of AI and deep learning in reproductive medicine, overcoming these barriers will allow rapid predicting capabilities, identification mechanisms, and analysis of sperm integrity done in real time, without the need of samples being stained for identification purposes ( Table 2 ) [ 4 , 7 , 10 , 11 , 13 , 14 , 17–24 , 28 , 31 , 33 , 36–39 , 41 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROIs were located at the embryo decidua basalis. Related parameters obtained through the time intensity curve (TIC) included arrival time (AT, the time from injection of the agent to the point when the first contrast bubbles appeared in the gestational sac), peak intensity (PI, the maximal intensity of the TIC), and area under the curve around the gestational sac (AUC, the area under the TIC) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…86 Since then, only two recent studies have focused on determining the usefulness of CEUS in infertility, by investigating whether it could be used to predict the success rate of testicular sperm retrieval techniques in infertile men. 37,38 Zhang et al evaluated whether CEUS could be considered as a noninvasive approach for detecting the testicular area where spermatogenesis is most likely to be found in nonobstructive azoospermic testes. Among the 187 testes that underwent microdissection TESE, the sperm retrieval rates of the best perfusion area over the maximal longitudinal section were higher than those with the poorest perfusion area and conventional area where TESE is usually performed (63.1% vs. 34.7% and 47.1% respectively, p < 0.05).…”
Section: Infertilitymentioning
confidence: 99%